THE EFFECT OF COUNTRY OF ORIGIN EFFECT ON PURCHASE INTENTION - Vincensius Januas; Muhammad Idrus Taba; Sarwo Edy Handoyo (Graduate Program of Universitas Tarumanagara, 2026)
In the context of the global market, this study incorporates recent empirical data on the impact of Country of Origin (COO) on consumer purchase intention. It maps both direct and indirect relationships between COO and consumer behavior through a comprehensive systematic literature review of journal articles published between 2019-2024. Across various product categories and geographic regions, findings consistently show that COO exerts a positive and significant influence on purchase intention. Perceived quality and trust emerge as key mediating factors, with the effect often being indirect. The primary linkage lies in perceived quality, where a favorable perception of a product’s country of origin enhances perceived quality, which in turn drives purchase intention. Moreover, the COO effect is conditional, as moderating variables such as consumer ethnocentrism can weaken the positive influence of foreign product origins. This study concludes by proposing an integrated conceptual model that captures the comprehensive dynamics of consumer decision-making, incorporating both mediating and moderating roles as part of a contemporary understanding of the COO effect. The implications highlight the importance of marketing strategies that account for consumer perceptions and the unique characteristics of target markets.